Statistical studies of financial reports and stock markets - Shyam Sunder (Journal of Capital Markets Studies (JCMS), 2017)
Purpose - The purpose of this paper is to examine the usefulness of statistical studies of financial reports and stock market data for improving corporate financial reports. Design/methodology/approach - Analytical writing. Findings - It is often claimed that statistical studies of co-variation between financial and stock market data can help set better financial reporting policy. Such co-variation, even when it can be estimated, tells us little about which financial reports help to make better financial decisions. A case in support of such claims remains to be made. Practical implications - The readers are advised to be extremely careful in drawing inferences from studies of co-variation between accounting and stock market data for financial reporting policy. Social implications - Inference from accounting empirical studies to policy needs better rationale to avoid bad policy consequences. Originality/value - This paper raises original questions about policy inferences from a large class of empirical research in accounting.
Keywords: M41; 330; Efficient markets; Financial reporting policy; Statistical co-variation